Captain Underpants and the big, bad battle of the Bionic Booger Boy, part 1 : the night of the nasty nostril nuggets - Pilkey, Dav, 1966- (Pilkey, Dav, 1966- Captain Underpants ;, 2018)
A snotty situation ensues when Melvin Sneedley, an academically-gifted student, turns into the Bionic Booger Boy and must be stopped by George, Harold, and Captain Underpants.